2015
DOI: 10.5380/avs.v20i1.35847
|View full text |Cite
|
Sign up to set email alerts
|

Níveis Séricos De Triiodotironina (T3) E Tiroxina (T4) Em Ovelhas Com Toxemia Da Prenhez.

Abstract: trabalho tem por objetivo verificar os níveis séricos hormonais de triiodotironina (T3) e tiroxina (T4) em ovelhas diagnosticadas com toxemia da prenhez (TP), bem como avaliar sua participação e reflexo neste tipo de transtorno metabólico. Foram analisadas as fichas clínicas de 24 ovelhas atendidas na Clínica de Bovinos, Campus Garanhuns/UFRPE, diagnosticadas com TP, no período de 2007 a 2012. Os animais foram submetidos ao exame clínico e ultrassonográfico, seguido de coleta de sangue e urina para exames labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…In addition, results of Macedo et al (2015), who concluded that clinical PT in sheep causes marked changes in the metabolism of these hormones. According to Hefnawy et al (2011), who also found a significant decrease in T4 in goats with clinical PT, this reduction is possibly related to an excessive secretion of cortisol, characterizing a negative correlation between these variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, results of Macedo et al (2015), who concluded that clinical PT in sheep causes marked changes in the metabolism of these hormones. According to Hefnawy et al (2011), who also found a significant decrease in T4 in goats with clinical PT, this reduction is possibly related to an excessive secretion of cortisol, characterizing a negative correlation between these variables.…”
Section: Discussionmentioning
confidence: 99%
“…The significant βHB elevation from the 20 th dap onwards observed in the G3 group is associated with an inability to meet energy demands at the end of pregnancy due to rapid fetal growth (Macedo et al, 2015;Souto et al, 2013). This elevation was observed to be three times the initial value prepartum until parturition.…”
Section: Discussionmentioning
confidence: 99%
“…The lower values of TP, albumin, and globulin in animals with clinical and subclinical PT, when compared to the control group, demonstrated the influence of the metabolic disorder on these variables. However, the absence of changes in the concentration of TP and albumin has been reported in the clinical form (16,19) and in the subclinical form of PT (8) .…”
Section: Protein Profilementioning
confidence: 98%
“…Os valores inferiores da PT, da albumina e da globulina nos animais com TP clínica e subclínica, quando comparados ao grupo controle demonstraram haver influência do distúrbio metabólico nestas variáveis. No entanto, a ausência de alteração na concentração da PT e da albumina foi relatada na forma clínica da TP (16,19) e na forma subclínica (8) .…”
Section: Perfil Proteicounclassified